2013
DOI: 10.1002/pi.4666
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(propylene glycol) polytrioxamide and poly(urea oxamide) segmented copolymers

Abstract: This report describes the synthesis and characterization of unprecedented poly(propylene glycol) (PPG) polytrioxamide and poly(urea oxamide) (UOx) segmented copolymers containing monodisperse hard segments. Synthesis of the segmented copolymers relied on an efficient two‐step end‐capping sequence, which resulted in novel difunctional oxamic hydrazide‐terminated polyether oligomers. Polymerization with oxalyl chloride or 4,4′‐methylenebis(cyclohexyl isocyanate) provided the desired segmented copolymers displayi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Poly(urea oxamide) copolymers also demonstrated a higher Young's moduli and stress at break, but a decrease in the strain at break resulted. [113,115] Oxamide …”
Section: Poly(oxamide) Segmented Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly(urea oxamide) copolymers also demonstrated a higher Young's moduli and stress at break, but a decrease in the strain at break resulted. [113,115] Oxamide …”
Section: Poly(oxamide) Segmented Copolymersmentioning
confidence: 99%
“…PTMObased poly(oxamide)s also showed a high moduli >120 MPa with stress and strain at break up to , copolymer composition and level of crystallinity greatly affected the mechanical properties [114]. DMA revealed long, temperature-insensitive, service windows up to 180 ˚C for PDMS poly(oxamide) copolymers, and the rubbery plateau length and storage moduli varied with copolymer composition(Figure 17) [111,113,114] [111]. Recent reports include the structure-property relationships of poly(oxamide) copolymers for both PTMO and PDMS based copolymers.…”
mentioning
confidence: 96%
“…[34] The appearance of a shoulder in the CO stretch as temperature increased could also indicate that a shift from ordered to disordered hydrogen bonds also occurred. Previous work in our laboratories studying oxamide‐containing copolymer revealed a similar presence of disordered hydrogen bonds with increasing temperature . Thus, the transition observed by DSC at ≈70 °C likely corresponded to the dissociation of amide hydrogen bonding due to the incorporation of the MBAm comonomer.…”
Section: Resultsmentioning
confidence: 52%
“…Previous work in our laboratories studying oxamide-containing copoly mer revealed a similar presence of disordered hydrogen bonds with increasing temperature. [46][47][48] Thus, the transition observed by DSC at ≈70 °C likely corresponded to the dissociation of amide hydrogen bonding due to the incorporation of the MBAm comonomer. The high temperature of the transition (70 °C) indicated that the material should maintain mechanical integrity at body temperature despite being well above T g .…”
Section: Variable Temperature Fitr Studiesmentioning
confidence: 99%
“…In this study, the saturated water absorption of PA52 is measured to be 3.2 wt%, which is only about one third of that of PA6 (about 10 wt% ) and about one fourth of PA46 (12.4 wt% ). This low saturated water absorption should be mainly attributed to the unique adjacent double hydrogen‐bonds in POA and high crystallinity of PA52, which gives it better dimensional stability compared with PA6.…”
Section: Resultsmentioning
confidence: 99%